Knowledge and misconceptions about the causes of climate change: a cross sectional study - Alvarado Yepéz, Andy J. (2019)
Knowledge of climate change is a necessary condition for the understanding of this phenomenon and thus for the generation of environmental behaviors, however, the knowledge of the causes is still a debatable area regarding correct and erroneous conceptions. The present research aims to analyses the correct knowledge and misconceptions about the anthropogenic causes that contribute to climate change. The sample consisted of N= 250 subjects from the city of Cusco, Peru. Regarding the knowledge that causes climate change, it is observed that most of the participants identify the burning of fossil fuels, the increase of carbon dioxide, deforestation, and the fact of driving a car as the most relevant. On the other hand, misconceptions related to climate change were toxic waste, nuclear power plants, aerosol cans, ozone hole. In the group analysis, significant differences were found with respect to occupation (between housewives and professionals), and education (secondary and technical level). However, gender, age and income were not significant. Finally, the implications of misconceptions and misconceptions on the development of awareness of climate change risks, and levels of engagement and participation in adaptation and mitigation strategies are discussed.